Strengthening Anti-Bullying Character in Elementary School Students Through the Integration of Values of Compassion and Brotherhood in Short Surahs of the Qur'an - Dariyanto; Awiria (International Conference on Elementary Education, 2025)
Bullying in elementary education poses a significant threat to student psychological well-being and academic safety, requiring urgent pedagogical solutions. This study aims to explore the strategic integration of the Islamic values of compassion (rahmah) and brotherhood (ukhuwah), derived specifically from Surah Al-Ma'un and Al-'Asr, to strengthen anti-bullying character education. Employing a qualitative case study design at SDIT Ibnu Majah in Bekasi. The data was collected through triangulated methods, including structured interviews, observation, and document analysis. The results reveal that thematically integrating these Qur'anic values highlighting the obligations to assist the vulnerable and the prohibition of belittling others was proven effective in significantly building students' emotional awareness and cultivating a profound sense of empathy. The study identified that key implementation strategies deliberately moved beyond traditional rote memorization, instead utilizing interactive storytelling and role-playing to foster a deep, practical internalization of social ethics. In sum, the research concludes that contextualizing religious values of compassion and brotherhood is essential for comprehensively strengthening anti-bullying character. By formulating standards of behavior through reference to spiritual principles, educators can establish a sustainable culture of mutual respect, suggesting that faith-based interventions offer a vital framework for mitigating interpersonal aggression and hostility among young learners.